2009
DOI: 10.1080/14763140903229518
|View full text |Cite
|
Sign up to set email alerts
|

Total kinetic energy production of body segments is different between racing and training paces in elite Olympic rowers

Abstract: Total kinetic energy (TKE) was calculated for 28 Canadian national team Olympic rowers during training on water, comparing low-stroke rates (18-22 stroke/min) and high-stroke rates (32-40 stroke/min), using video analysis. Stroke duration was normalized to 100%, beginning and ending at the "catches", with the drive phase occurring first and recovery second. Two discrete points were identified during the stroke, both occurring when the fingers had the same horizontal position as the ankles (i.e., mid-drive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
0
6
0
4
Order By: Relevance
“…The dynamic differences between high and low rowing intensities have previously been highlighted for on-water rowing. In 28 elite Canadian rowers, total kinetic energy during the Lower back loads in elite rowers 7 recovery phase was six times greater during high intensity rowing and approximately equal to the kinetic energy required during the drive phase (Bechard, Nolte, Kedgley, & Jenkyn, 2009). As the results from this study also suggests, high intensity rowing places greater demands on the body during the recovery phase, compared to rowing at a lower intensity.…”
Section: Discussionmentioning
confidence: 97%
“…The dynamic differences between high and low rowing intensities have previously been highlighted for on-water rowing. In 28 elite Canadian rowers, total kinetic energy during the Lower back loads in elite rowers 7 recovery phase was six times greater during high intensity rowing and approximately equal to the kinetic energy required during the drive phase (Bechard, Nolte, Kedgley, & Jenkyn, 2009). As the results from this study also suggests, high intensity rowing places greater demands on the body during the recovery phase, compared to rowing at a lower intensity.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the increasing volume of research into segmental sequencing in the golf swing, there is still little agreement regarding the most appropriate analysis technique. The examination of segment kinetic energy (KE) is increasingly popular in scientific studies to examine the effectiveness of movement patterns (Bechard, Nolte, Kedgley & Jenkyn, 2009;Ferdinands, Kersting & Marsdhall, 2012;Slawinski et al, 2010). It has been suggested that the analysis of segment KE is the most appropriate technique to examine the sequencing of body segments (Anderson, Wright & Stefanyshyn, 2006;Bechard et al, 2009;Ferdinands et al, 2012;Slawinski et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The examination of segment kinetic energy (KE) is increasingly popular in scientific studies to examine the effectiveness of movement patterns (Bechard, Nolte, Kedgley & Jenkyn, 2009;Ferdinands, Kersting & Marsdhall, 2012;Slawinski et al, 2010). It has been suggested that the analysis of segment KE is the most appropriate technique to examine the sequencing of body segments (Anderson, Wright & Stefanyshyn, 2006;Bechard et al, 2009;Ferdinands et al, 2012;Slawinski et al, 2010). As well as incorporating inertial parameters, distal segment speed in striking and throwing movements has frequently been associated with the magnitude, timing and transfer of segment KE (Cole & Grimshaw, 2016;Ferdinands, 2011;Slawinski et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations